2009
DOI: 10.1177/0363546509337578
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Kinematics of the Tibiotalar Joint After Lateral Ankle Instability

Abstract: BACKGROUND Previous studies have suggested injury to the anterior talofibular ligament may be linked to altered kinematics and the development of osteoarthritis of the ankle joint. However, the effects of ATFL injury on the in vivo kinematics of the ankle joint are unclear. HYPOTHESIS Based on the orientation of the ATFL fibers, we hypothesized that ATFL deficiency would lead to increased anterior translation and increased internal rotation of the talus relative to the tibia. STUDY DESIGN Controlled labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
180
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(192 citation statements)
references
References 50 publications
11
180
1
Order By: Relevance
“…The exact mechanism of joint degeneration is unclear but likely due to both inflammatory factors and altered biomechanics. 78 Mechanical ankle instability (MAI) is a result of a ligamentous tear that results in pathological joint laxity 79 while CAI has been defined as a recurrent giving away of the ankle that occurs for greater than 1 year after an ankle sprain. 80 The CAI patient may present with pain, 81 recurrent ankle sprains, 82 diminished neuromuscular control, 83 weakness, 84 impaired joint position sense, 84 and decreased performance and self-report of functional and sport activity.…”
Section: Anklementioning
confidence: 99%
“…The exact mechanism of joint degeneration is unclear but likely due to both inflammatory factors and altered biomechanics. 78 Mechanical ankle instability (MAI) is a result of a ligamentous tear that results in pathological joint laxity 79 while CAI has been defined as a recurrent giving away of the ankle that occurs for greater than 1 year after an ankle sprain. 80 The CAI patient may present with pain, 81 recurrent ankle sprains, 82 diminished neuromuscular control, 83 weakness, 84 impaired joint position sense, 84 and decreased performance and self-report of functional and sport activity.…”
Section: Anklementioning
confidence: 99%
“…Unlike Nyska et al, 37 we only observed a significant positive association between the clinical grades of laxity determined with the ADT and the amount of anterior laxity measured with the arthrometer in the group with acute lateral sprains. Caputo et al 8 also identified only a slight amount of anterior talar translation (0.2-0.4 mm) in control ankles, in contrast to a significant amount of anterior translation (0.9  0.6 mm) in individuals with chronic ankle instability, when measured in weight bearing using a 3-D magnetic resonance imaging and orthogonal fluoroscopic imaging method. Hubbard 24 documented a 5.5-mm increase in anterior ankle laxity following acute ankle sprain and also indicated that perceptible anterior laxity and symptoms of instability may persist for more than a year following an ankle sprain.…”
mentioning
confidence: 97%
“…Alterations in fibular position, 26 as well as talar internal rotation and anterior displacement, which were not measured in this study, may explain the changes in the relative position of the bony landmarks. 8 We evaluated the laxity grade given with manual performance of the ADT against 2 standards of anterior talocrural laxity. The first standard was derived from the work of Kerkhoffs et al 31 and represents the results of 9 in vitro ligamentsectioning studies specifically designed to measure changes in talar motion in response to simulated ATFL injuries.…”
mentioning
confidence: 99%
“…[5][6][7] One such tool used to create these 3D models is Rhinoceros (McNeel and Associates, Seattle, WA). Rhinoceros creates a 3D model based on 2D semiautomated manual tracings of objects on 2D MRI slices.…”
Section: Introductionmentioning
confidence: 99%